2022
DOI: 10.1097/mco.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Validity and feasibility of the global leadership initiative on malnutrition diagnostic concept in older people: a literature review from August 2021 to August 2022

Abstract: Purpose of reviewEarly 2019, the Global Leadership Initiative on Malnutrition (GLIM) concept offered a clinically applicable and objective procedure for diagnosing malnutrition. This review summarizes 40 publications from August 2021 to August 2022 that applied the GLIM criteria in older populations from various clinical settings for criterion and predictive validation. Recent findingsCriterion validity studies, by comparing the GLIM construct with various semi-gold standards such as SGA, PG-SGA, MNA-FF/SF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
(72 reference statements)
2
13
0
Order By: Relevance
“…Among the 198 participants, a significant association was identified between MNA ® -SF malnutrition and four items from the 24-item MOCL. Various nutritional screening tools have been developed (Cederholm & Barazzoni, 2023;Huang et al, 2022;Kaluźniak-Szymanowska et al, 2021;Matsumoto et al, 2020; An association between fatigue and malnutrition has already been reported (Azzolino et al, 2020;Franz et al, 2019); similarly, in the present study, 'Has fatigue due to extended mealtime' was associated with malnutrition. Possible reasons for this include timeconsuming and interrupted meals, which may result in reduced energy intake, hindering adequate nutrition and fluid intake, or increasing energy expenditure due to fatigue.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Among the 198 participants, a significant association was identified between MNA ® -SF malnutrition and four items from the 24-item MOCL. Various nutritional screening tools have been developed (Cederholm & Barazzoni, 2023;Huang et al, 2022;Kaluźniak-Szymanowska et al, 2021;Matsumoto et al, 2020; An association between fatigue and malnutrition has already been reported (Azzolino et al, 2020;Franz et al, 2019); similarly, in the present study, 'Has fatigue due to extended mealtime' was associated with malnutrition. Possible reasons for this include timeconsuming and interrupted meals, which may result in reduced energy intake, hindering adequate nutrition and fluid intake, or increasing energy expenditure due to fatigue.…”
Section: Discussionsupporting
confidence: 79%
“…Among the 198 participants, a significant association was identified between MNA ® ‐SF malnutrition and four items from the 24‐item MOCL. Various nutritional screening tools have been developed (Cederholm & Barazzoni, 2023; Huang et al., 2022; Kaluźniak‐Szymanowska et al., 2021; Matsumoto et al., 2020; van Bokhorst‐de van der Schueren et al., 2014), but only a few studies have examined the association between these tools and the signs, symptoms and conditions during mealtime in LTC populations. To the best of our knowledge, this study is the first to investigate the association between a malnutrition screening tool and a checklist specifically focused on signs, symptoms and conditions during mealtime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches include consideration of underlying disease that may serve as a proxy for inflammation; examples include the Academy of Nutrition and Dietetics (AND) and American Society for Parenteral and Enteral Nutrition (ASPEN) Indicators to Diagnose Malnutrition (AAIM), 26 Nutritional Risk Screening (NRS)-2002, 27 Subjective Global Assessment (SGA), 28,29 and Patient-Generated SGA. 30 A recent review of GLIM studies in older adults found that a variety of approaches were being used for assessment of inflammation 31 ; more than half used the diagnosis of inflammatory disease only, whereas the others mainly used CRP alone or combined with the presence of inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of the GLIM criteria, numerous articles have been published assessing their validity or feasibility [ 13 ]. However, the number of studies conducted on institutionalized psychogeriatric patients remains limited.…”
Section: Introductionmentioning
confidence: 99%